Perbedaan Keragaman Pangan, Pola Asuh Makan, dan Asupan Zat Gizi Makro pada Balita dari Ibu Bekerja dan Ibu Tidak Bekerja - Hesti Permata Sari; Lilis Permatasari; Widya Ayu Kurnia Putri (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
Background: Toddlers are a group that is vulnerable to experiencing nutritional problems. The nutritional status of toddlers is very dependent on the role of caregivers, especially mothers. Business women have less time together with toddlers so that it will have an impact on mothers' attention to the growth and development of toddlers, child feeding patterns, food diversity, and macro-nutrient intake of toddlers. Research in Padang states that business women have a 1,3 times risk of experiencing malnutrition in children. Purpose: Know the differences in child feeding patterns, food diversity, and macro nutrient intake in toddlers from business women and housewife. Method: The design of this study was an observational analytic with cross sectional approach. The research was conducted on medium socioeconomic housing in Banyumas Regency. The sample are toddlers aged 12-59 months as many as 78 toddlers, taken using total sampling techniques. Data were statistically tested using independent T tests. Results: The results of study showed no differences in child feeding patterns (p = 0.605), food diversity (p = 0.767), energy intake (p = 0.483), protein intake (p = 0.806), fat intake (p = 0.787) and carbohydrate intake (p = 0.337) in toddlers from business women and housewife. Conclusions: There were no differences in child feeding patterns, food diversity, and macro nutrient intake in toddlers from business women and housewife.